Analysis of Student Cognitive Ability using The K-Means Cluster and Rasch Model (Winsteps) on Chemical Materials through Zoom Meeting - Azhari Umar Siregar; Asnarni Lubis; Ayi Darmana; Retno Dwi Suyanti (Universitas Veteran Bangun Nusantara, 2022)
This study aims to determine students' learning difficulties in chemistry by using zoom in achieving cognitive, sociological and psychological aspects and to further examine the difficulties faced by students. Data collection using questionnaires and tests, then using the K-Means Cluster data analysis technique, with three clusters (groups) followed by crosstab and graph analysis, using SPSS IBM 22 and followed by the RASH model. the results obtained are that (a) cognitive aspects in the form of student thinking, followed by sociological aspects and psychological aspects related to students' internal factors (b) cognitive results are tested more deeply with the Expended Score Graph. The ICC is in accordance with the RASH Model, the difficult questions to work on are questions 10 and 13 are in the analysis (C4), the Outfit MNSQ value is between 0.5-0.15 and then from the Probability graph of Student Cognitive Ability is well distributed, thus the difficulty in the cognitive aspect lies in the questions presented. These results are very useful for identifying students' cognitive limitations in chemistry learning. Thus, from the results, it is explained that cognitive is the main difficulty, with the RASCH test it is known that the level of difficulty is at the analysis.